Rancang Bangun Sistem Informasi Kelola Dokumen Berbasis Website Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Jawa Timur - Muhammad Zakky Ulil Amry; Chandra Febryan Saputra; Jonathan Alexander Christian; Abdul Rezha Efrat Najaf (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
Document management plays a key part in how government institutions run their administrative processes and information services, yet at the Department of Manpower and Transmigration of East Java Province it was still handled through physical archives and digital files scattered across different locations, making retrieval slow and inconsistent. This study designs and develops a web-based document management information system using the Waterfall method, built with the Laravel framework and MySQL as the database. Development covered requirements analysis, system design, implementation, and Black Box Testing, resulting in a system that provides document management, category and document type management, document relationship management, publication, search, and usage statistics. Testing results showed that all functions worked according to the specified requirements, resolving the fragmentation that had previously slowed down the institution's document-handling process.